(untitled) (Al-Qamar, 2022)
Visual Communication is a strong tool to represent the corporate identity. Logo design is the second important thing in branding. Religion Islam encourages us to mark identity to our belongings, individuals, and goods. In this account Prophet Muhammad (s.a.w) set the examples in his life. Pakistan is the second-largest Islamic country and Islamic history leaves an impression on the branding strategies. This research paper will discuss the logo design of Pakistan. Further will study the strategy of companies in the selection of symbols, icons, typography for the emblem, and wordmark of the logo. To analyze the data Content Analysis methodology has been used for this paper, in which logos of the educational sector and banking sector has been selected. Data was collected from secondary sources like official websites and prior research. The study indicates that how Islamic roots of all Islamic countries are connected and follow the Islamic symbols, icons, scripts, and colours to communicate with the consumers.